INCREASED MOTIVATION AND RESULTS OF STUDENT MATH LEARNING THROUGH REALISTIC MATHEMATICS EDUCATION - Wiwin Rita Sari; Siti Mutmainah (Universitas Sembilanbelas November Kolaka, 2018)
The purpose of this study was to determine the increase motivation and results of students' mathematics learning through Realistic mathematics Education approach. The study was conducted at VIII A grade students of SMP Ma'arif 01 Seputih Raman Central Lampung in geometry material. This type of research is classroom action research. The research was conducted during two cycles with each cycle consisting of the stages of planning, action, observation, and reflection. Instruments used include questionnaires motivation to learn mathematics, observation sheets, and assessment test. Data analysis techniques using descriptive quantitative analysis obtained by converting scores into qualitative criteria. Results from this study are the increased motivation to learn mathematics students from pre-cycle to the second cycle. The result of Student Mathematics learning also increased successively from the pretest to the second cycle average of 62.88 students' mathematics learning outcomes; 76.82; and 81.36. Classical completeness obtained was 72.7%. In general implementation of learning by applying Realistic Mathematics Education approach can improve motivation and results of students' mathematics learning.